A kind of formaldehyde-free powder coating for MDF and its preparation method and application

By using hydrothermal treatment and ultrasonic dispersion in MDF powder coatings, silicon titanium self-detergent prepared with hydrothermal treatment and ultrasonic dispersion, combined with epoxy resin and polyester resin, the formaldehyde release and side cracking of MDF materials are solved, achieving efficient formaldehyde removal and improved coating Low-temperature curing powder coating for layer properties.

CN118308009BActive Publication Date: 2025-01-03KAIFENG RUIZHI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410495561.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-01-03
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

During use, the MDF of medium-density fiberboard is prone to cracking, warping and deformation of the side, and the urea formaldehyde resin used during the preparation process leads to formaldehyde release, causing indoor environment pollution. The existing formaldehyde removal powder coatings are poor in effect and have storage stability and Application performance has a negative impact.

Method used

Using powder coatings including epoxy resin, polyester resin, titanium silicon self-detergent, barium sulfate, leveling agent and benzoin, silicon titanium silicon self-detergent is prepared by hydrothermal treatment and ultrasonic dispersion, combining 2-methyl Curing catalysts such as imidazole are sprayed on the MDF surface at low temperature, and the curing temperature is between 130-160℃ to improve formaldehyde removal effect and coating performance.

Benefits of technology

It achieves the improvement of formaldehyde removal effect and coating performance of MDF powder coating under low temperature curing conditions, significantly reduces the indoor formaldehyde content, while maintaining the leveling, impact resistance and wear resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004806920350000101
    Figure BDA0004806920350000101
  • Figure BDA0004806920350000111
    Figure BDA0004806920350000111
Patent Text Reader

Abstract

The present invention relates to a MDF formaldehyde-free powder coating, which comprises the following components by weight: 50-70 parts of epoxy resin, 50-70 parts of polyester resin, 3-6 parts of curing accelerator, 2-10 parts of silicon-titanium self-cleaning agent, 10-40 parts of barium sulfate, 1-4 parts of leveling agent, and 1-4 parts of benzoin. The present invention also discloses a silicon-titanium self-cleaning agent and a preparation method for the MDF formaldehyde-free powder coating. The MDF formaldehyde-free powder coating disclosed by the present invention has low curing temperature, excellent formaldehyde removal effect, and also has a lasting formaldehyde removal effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a powder coating for medium density fiberboard (MDF), in particular to a formaldehyde-free powder coating for medium density fiberboard (MDF) and a preparation method and application thereof. Background Art

[0002] Medium-density fiberboard (MDF) is the mainstream base material for powder-coated wooden furniture. Unlike metal base materials, MDF is very prone to side cracking, warping, and reduced mechanical strength at high temperatures. Therefore, MDF powder coatings must be melt-leveled and cured at a relatively low temperature to prevent the base material from being damaged by high temperatures. In recent years, low-temperature curing powder coatings have also been continuously improved, with the curing temperature reduced from the original 160°C to 120-140°C. Low-temperature curing powder coatings are becoming more and more popular for coating MDF boards.

[0003] On the other hand, MDF boards use a lot of urea-formaldehyde resin for bonding during the preparation process, and urea-formaldehyde resin contains a high content of formaldehyde. MDF furniture boards will continuously release formaldehyde during use, which will cause indoor environmental pollution. Therefore, it is urgent to develop powder coatings for MDF with formaldehyde removal function.

[0004] Common formaldehyde removal materials include tourmaline, opal, diatom mud and other negative ion releasing materials. Adding the above materials to the coating composition can give the coating a certain degree of formaldehyde removal performance. However, directly adding negative ion additives to the coating will not have a satisfactory formaldehyde removal effect on the resulting coating, and may even have a certain adverse effect on the storage stability and application performance of the coating.

[0005] Patent CN103289540A discloses a plastic powder coating that releases negative ions, which includes polyester resin, epoxy resin, pigment filler and negative ion additives, and the negative ion additives include tourmaline, opal and ice stone. The negative ion additive can release negative ions, thereby playing the role of antibacterial and air purification. The negative ion releasing powder coating is sprayed on the surface of household appliances to obtain a coating, and the coating releases negative ions under changes in temperature or pressure, thereby preventing bacteria from surviving on the coating surface and removing indoor formaldehyde.

[0006] Patent CN104497795A discloses a negative ion-releasing antibacterial powder coating, which includes epoxy resin, polyester resin, negative ion additive, nano-silver antibacterial agent, filler, additive, etc. The coating obtained by the invention can effectively release negative ions and has excellent bactericidal effect. Moreover, the anti-cracking, adhesion, bending resistance and other properties of the obtained powder coating exceed those of conventional powder coatings.

[0007] Patent CN105599419A discloses a formaldehyde-free and antibacterial melamine-impregnated paper composite material, and discloses a nano-silicon-titanium self-cleaning agent and its preparation method. The nano-silicon-titanium self-cleaning agent is made by mixing melamine, formaldehyde, nano-silver, opal, titanium dioxide and other raw materials, dispersing them through high-pressure spraying, and grinding them into a nano-silicon-titanium self-cleaning agent. The invention points out the synergistic effect of physical adsorption and photocatalytic degradation of the porous "molecular sieve" structure of the nano-silicon-titanium self-cleaning agent. The wood composite material can continuously and long-term play the function of formaldehyde removal and antibacterial in the whole process of production, sales and use. The formaldehyde removal rate of the product reaches 60-85% within 24 hours, and the antibacterial effect reaches 90-99.99%.

[0008] Patent CN108360778A discloses a decorative sheet material capable of long-term continuous decomposition of formaldehyde and its production process, which uses an adhesive containing formaldehyde decomposing elements including nano-silicon titanium and nano-titanium dioxide between the substrate and the decorative paper. The invention uses nano-silicon titanium and nano-titanium dioxide as the main raw materials to make a composite formaldehyde-removing agent, the formaldehyde purification efficiency of the composite formaldehyde-removing agent can reach 90%, and the formaldehyde purification durability is 64.7%. The composite formaldehyde-removing agent plays a synergistic purification and decomposition role of the two main formaldehyde-removing materials. However, the invention does not disclose the source or composition of nano-silicon titanium.

[0009] Patent CN109354820A discloses an antibacterial ecological foam board, which is prepared from nano-silicon titanium self-cleaning agent, biodegradable resin, phenolic resin and other raw materials. However, the invention does not disclose the composition of the nano-silicon titanium self-cleaning agent, nor does it disclose the effect of the nano-silicon titanium self-cleaning agent on the performance of the foam board.

[0010] Patent CN117165150A discloses a low-temperature curing formaldehyde-removing powder coating for MDF and its application process. The coating includes powder 1 and powder 2 components. Powder 1 includes low-temperature curing polyester, epoxy resin, pigments, fillers and additives, and powder 2 includes low-temperature curing additives and formaldehyde-removing functional materials. The formaldehyde-removing functional materials include at least one of formaldehyde-removing powder, diatomaceous earth, photocatalyst, and formaldehyde scavenger, or a composite product. The coating obtained by the invention is applied to MDF boards, so that the MDF boards have the purpose of continuous formaldehyde removal and air purification, which greatly solves the problem of indoor air pollution. However, the formaldehyde-removing functional material used in the invention is a common low-efficiency formaldehyde-removing material, and the formaldehyde-removing effect of the obtained coating needs to be further improved.

[0011] Patent CN110653895A discloses a negative oxygen ion ecological board and its production method. After crushing nano silicon titanium and natural opal, stirring and adsorbing with clean formaldehyde mud, and then coating the surface of the board, nano silicon titanium and natural opal are both natural mineral extracts, and no harmful substances and pollution are produced during the adsorption and decomposition of formaldehyde. It is evenly distributed on the surface of the decorative board, and can continuously and long-term play the function of clean formaldehyde and antibacterial through the process of capturing adsorption, decomposition, and re-adsorption and decomposition. However, the composite material disclosed in the invention only includes inorganic raw materials such as nano silicon titanium, Ye Shell Carbon particles, diatom mud, opal, etc., and the film-forming type is poor, and it is difficult to obtain a negative oxygen ion ecological board with good application performance. Summary of the invention

[0012] In order to achieve the above object, the present invention discloses a formaldehyde-free powder coating for MDF, which comprises the following components in parts by mass:

[0013] 50-70 parts of epoxy resin, 50-70 parts of polyester resin, 3-6 parts of curing accelerator, 2-10 parts of silicon-titanium self-cleaning agent, 10-40 parts of barium sulfate, 1-4 parts of leveling agent, and 1-4 parts of benzoin.

[0014] The epoxy resin is one or more of E-06, E-12, and E-20 epoxy resins.

[0015] The acid value of the polyester resin is 30-60 mgKOH / g. Further, the acid value of the polyester resin is 45-60 mgKOH / g.

[0016] Preferably, the polyester resin is specifically selected from one or more of DSM Uralac P3050, Excalibur SJ6711, and Excalibur SJ6722.

[0017] Furthermore, the mass ratio of the epoxy resin to the polyester resin is 0.7:1-1:0.7.

[0018] Furthermore, the weight proportion of the silicon-titanium self-cleaning agent may be 3-10 parts, or 3-8 parts.

[0019] The curing catalyst is selected from any one of 2-methylimidazole, 2-phenylimidazole and 2-ethyl-4-methylimidazole.

[0020] The barium sulfate has a particle size of 400-1000 meshes. The leveling agent is a polyacrylate leveling agent.

[0021] Barium sulfate, leveling agent and benzoin were all purchased from the market.

[0022] The raw materials for preparing the silicon-titanium self-cleaning agent include opal, a silicon source, a titanium source and a metal salt of an antibacterial nano material.

[0023] The opal is a porous opal that has been hydrothermally treated and has a particle size of 200-600 meshes.

[0024] The silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, aminopropyl trimethoxysilane, aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane.

[0025] The titanium source is one or more of tetraethyl titanate, tetrabutyl titanate, and tetraisopropyl titanate.

[0026] The antibacterial nano material is nano silver.

[0027] The preparation method of the silicon-titanium self-cleaning agent comprises the following steps:

[0028] Step 1, respectively add a silicon source and a titanium source to an ethanol aqueous solution containing an acid, and carry out a hydrolysis condensation reaction for 4-12 hours to obtain a silica sol and a titanium sol for standby use.

[0029] Step 2, dispersing the opal powder in deionized water containing sodium aluminate and sodium tripolyphosphate by ultrasonic vibration to obtain a mixed solution 1. Then placing the mixed solution 1 in a hydrothermal reactor for hydrothermal reaction, centrifuging and separating the mixture after the hydrothermal reaction to obtain a solid, grinding and sieving the solid to obtain a porous opal with a particle size of 200-600 mesh.

[0030] Step 3, under light-proof conditions, dissolve the metal salt of the antibacterial nanomaterial in a methanol solution, then add silica sol and titanium sol thereto, stir for 2-5 hours, add porous opal, continue stirring for 2-6 hours, and obtain a mixed solution 2. Then add a sodium borohydride aqueous solution to the mixed solution 2, stir at high speed for 2-4 hours, separate the solids by centrifugation, wash the solids, and vacuum dry them to obtain a silicon-titanium self-cleaning agent.

[0031] The acid is one or more of hydrochloric acid, acetic acid and phosphoric acid.

[0032] The mass percentage of ethanol in the ethanol aqueous solution is 40%-80%.

[0033] The metal salt of the antibacterial nano material is silver nitrate.

[0034] The conditions of the hydrothermal reaction are a reaction temperature of 80-120° C. and a reaction time of 6-12 h.

[0035] The mass percentage of the silicon source and the titanium source in the silica sol and the titanium sol is 1-6%.

[0036] The mass ratio of the silica sol to the titanium sol is 0.5:1-1:1.

[0037] The mass percentage of opal powder in the mixed solution 1 is 5-25%.

[0038] The mass percentage of sodium aluminate and sodium tripolyphosphate in the mixed solution 1 is 0.2-0.8%.

[0039] The mass percentage of the metal salt of the antibacterial nano material in the mixed solution 2 is 0.5-2%, the mass percentage of the silica sol and the titanium sol are both 20-40%, and the mass percentage of the porous opal is 5-20%.

[0040] The molar concentration of the sodium borohydride aqueous solution added to the mixed solution 2 is 0.5 mol / L, and the mass ratio of the mixed solution 2 to the sodium borohydride aqueous solution is 100:2-8.

[0041] The present invention also discloses a method for preparing a formaldehyde-free powder coating for MDF, which comprises the following steps:

[0042] Step S1: weighing various raw material components of the powder coating according to the preparation formula, adding them into a mixer, and mixing them evenly to obtain a mixture;

[0043] Step S2: adding the mixed material into a twin-screw extruder for extrusion at a temperature of 80-110° C.;

[0044] Step S3: tabletting, cooling, crushing, and screening the extruded material, and selecting D 50 The powder with a particle size of 30-50 μm is obtained as a finished powder coating.

[0045] The present invention also discloses an application of a formaldehyde-free powder coating for MDF, which is applied to the coating of medium-density fiberboard. The application comprises the following steps:

[0046] Step A, prepare the substrate and clean the surface of the MDF substrate;

[0047] Step B, spraying, spraying the powder coating on the surface of the MDF substrate using an electrostatic spray gun;

[0048] Step C, heating and curing, curing in an infrared heating furnace, curing conditions are 130-160° C., 15-30 minutes.

[0049] The beneficial effects of the present invention are as follows:

[0050] The present invention obtains a powder coating for MDF with low curing temperature and good application performance by selecting the types of epoxy resin and polyester resin in the powder coating. The present invention prepares a silicon-titanium self-cleaning agent, which has good compatibility with the powder coating and good dispersibility in the powder coating coating. In addition, the silicon-titanium self-cleaning agent has a lasting formaldehyde removal effect, which gives the powder coating a good formaldehyde removal effect. The formaldehyde removal powder coating is used for MDF board coating, which can effectively reduce the indoor formaldehyde content. Specific embodiments

[0051] The present invention will be further described below in conjunction with specific embodiments:

[0052] It should be understood that the specific embodiments described herein are part of the embodiments of the present invention, rather than all of the embodiments, and are merely used to explain the embodiments of the present invention, and are not used to limit the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0053] Preparation Example

[0054] Preparation of silicon titanium self-cleaning agent. The raw materials are as follows:

[0055] Opal, fine powder passing 800 mesh, Nenjiang County Mineral Products Development Co., Ltd.; common raw materials or chemical reagents such as ethyl orthosilicate, aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, tetrabutyl titanate, silver nitrate, sodium borohydride, etc. were purchased from the market.

[0056] Preparation method

[0057] Step 1, add 3 parts of silicon source and 3 parts of titanium source to 100 parts (by mass, the same below) of 60% ethanol aqueous solution (pH adjusted to 3 with hydrochloric acid) containing a small amount of hydrochloric acid, heat to 60°C, and undergo hydrolysis condensation reaction for 10 hours to obtain silica sol and titanium sol for use.

[0058] Step 2, dispersing 20 parts of opal powder in 100 parts of deionized water containing 0.5 parts of sodium aluminate and 0.5 parts of sodium tripolyphosphate by ultrasonic vibration to obtain a mixed solution 1. Then, the mixed solution 1 is placed in a hydrothermal reactor for hydrothermal reaction, and the mixture after the hydrothermal reaction is centrifuged and separated to obtain a solid, and the solid is ground and sieved to obtain a porous opal with a particle size of 400 mesh. The reaction temperature of the hydrothermal reaction is 90° C., and the reaction time is 8 hours.

[0059] Step 3, under light-proof conditions, dissolve 3 parts of silver nitrate in 100 parts of methanol solution, then add 25 parts of silica sol and 30 parts of titanium sol thereto, stir for 4 hours, add 15 parts of porous opal, continue stirring for 4 hours, and obtain mixed solution 2. Then add 4 parts of 0.5 mol / L sodium borohydride aqueous solution to mixed solution 2, stir at high speed for 2 hours, separate solids by centrifugation, wash the solids, and vacuum dry them at 80°C to obtain a silicon-titanium self-cleaning agent.

[0060] The selection of silicon source and titanium source in Preparation Example 1-7 is as follows:

[0061] Preparation Example 1: The silicon source is ethyl orthosilicate, and the titanium source is tetrabutyl titanate.

[0062] Preparation Example 2: The silicon source is aminopropyltriethoxysilane, and the titanium source is tetrabutyl titanate.

[0063] Preparation Example 3: The silicon source is γ-glycidyloxypropyltrimethoxysilane, and the titanium source is tetrabutyl titanate.

[0064] Preparation Example 4: The silicon source is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and the titanium source is tetrabutyl titanate.

[0065] Preparation Example 5: The silicon source is ethyl orthosilicate and aminopropyltriethoxysilane in a mass ratio of 1:1, and the titanium source is tetrabutyl titanate.

[0066] Preparation Example 6: The silicon source is tetraethyl orthosilicate and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 1:1, and the titanium source is tetrabutyl titanate.

[0067] Preparation Example 7: The silicon source is ethyl orthosilicate and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane in a mass ratio of 1:1, and the titanium source is tetrabutyl titanate.

[0068] Preparation Example 1-7 was prepared according to the above preparation method to obtain the silicon-titanium self-cleaning agent corresponding to Preparation Example 1-7.

[0069] Example

[0070] The silicon-titanium self-cleaning agent prepared in the preparation example and other raw materials of the powder coating are used to prepare the powder coating.

[0071] Epoxy resin E-12, Baling Petrochemical; polyester resin, Shenjian SJ6711; curing accelerator, 2-methylimidazole, Shanghai Langrui; silicon titanium self-cleaning agent, the above preparation example is self-made. Leveling agent, barium sulfate and benzoin are common raw materials, and their sources of acquisition are commercially available.

[0072] The preparation method of powder coating is as follows:

[0073] Step S1: weighing various raw material components of the powder coating according to the preparation formula, adding them into a mixer, and mixing them evenly to obtain a mixture;

[0074] Step S2: adding the mixed material into a twin-screw extruder for extrusion at a temperature of 100° C.;

[0075] Step S3: tabletting, cooling, crushing, and screening the extruded material, and selecting D 50 The powder with a particle size of 30-40 μm is the finished powder coating product.

[0076] The preparation formula of the powder coating of the embodiment and comparative example is as follows:

[0077] Example 1: 3 parts of epoxy resin E-125, 50 parts of carboxyl polyester resin, 3 parts of curing accelerator, 3 parts of silicon-titanium self-cleaning agent obtained in Preparation Example 1, 8 parts of barium sulfate, 2 parts of leveling agent, and 1 part of benzoin.

[0078] Example 2-7: The difference from Example 1 is that the silicon-titanium self-cleaning agent is prepared by Preparation Examples 2-7 respectively.

[0079] Comparative Example 1: The difference from Example 1 is that no silicon-titanium self-cleaning agent is added.

[0080] The difference between Comparative Example 2 and Example 1 is that the amount of silicon-titanium self-cleaning agent is reduced to 1 part.

[0081] Comparative Example 3: The difference from Example 1 is that the amount of silicon-titanium self-cleaning agent is increased to 12 parts.

[0082] Comparative Example 4: The difference from Example 1 is that a mixture of 3 parts of opal powder, nano-silver particles, nano-silicon dioxide and nano-titanium dioxide (the opal powder is untreated 400 mesh opal powder, the nano-silver is Xianfeng Nano XFJ14, the nano-silicon dioxide is Huifu HL-200, and the nano-titanium dioxide is Huifu photocatalyst titanium dioxide, and the mass ratio of the three in the mixture is 50:1:10:12) is used to replace the silicon-titanium self-cleaning agent.

[0083] The application method of the powder coating obtained in the above examples and comparative examples is as follows:

[0084] The powder coatings of the embodiment and the comparative example were sprayed on the surface of the cleaned MDF substrate using an electrostatic spray gun and cured in an infrared heating furnace at 140° C. for 30 min.

[0085] The test items, test methods and test results of the application performance of the coating are shown in Table 1.

[0086] Formaldehyde purification rate test method: Test the formaldehyde purification rate of the coating according to "JCT1074-2008 Purification Performance of Indoor Air Purification Functional Coating Materials".

[0087] Table 1: Coating performance test table.

[0088]

[0089]

[0090] From the test results of the above-mentioned embodiments and comparative examples, it can be known that the present invention first prepares a silicon-titanium self-cleaning agent including opal, silicon source, titanium source, and antibacterial nanomaterials, and then prepares a clean formaldehyde powder coating for MDF using epoxy resin, polyester resin, and silicon-titanium self-cleaning agent as raw materials. The experimental results of the embodiments and comparative examples prove that the application performance of the clean formaldehyde powder coating for MDF within the dosage range defined by the present invention meets the application performance requirements of the MDF powder coating, and the obtained powder coating has a good formaldehyde purification effect. If the dosage of the silicon-titanium self-cleaning agent is excessive, the leveling, impact resistance, and butanone resistance of the powder coating will deteriorate. Compared with directly mixing raw materials such as opal, nano titanium dioxide, and nano silver that have formaldehyde purification effects, the leveling, impact resistance, wear resistance, and formaldehyde purification rate of the powder coating obtained by the present invention are better.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A formaldehyde-free powder coating for MDF, comprising the following components by weight: 50-70 parts of epoxy resin, 50-70 parts of polyester resin, 3-6 parts of curing accelerator, 2-10 parts of silicon-titanium self-cleaning agent, 10-40 parts of barium sulfate, 1-4 parts of leveling agent, and 1-4 parts of benzoin; the raw materials for preparing the silicon-titanium self-cleaning agent include opal, silicon source, titanium source and metal salt of antibacterial nanomaterials; The preparation method of the silicon-titanium self-cleaning agent comprises the following steps: Step 1, respectively adding a silicon source and a titanium source to an ethanol aqueous solution containing an acid, and subjecting the solution to a hydrolysis condensation reaction for 4-12 hours to obtain a silica sol and a titanium sol for later use; Step 2, dispersing the opal powder in deionized water containing sodium aluminate and sodium tripolyphosphate by ultrasonic vibration to obtain a mixed solution 1, then placing the mixed solution 1 in a hydrothermal reactor for hydrothermal reaction, centrifuging and separating the mixture after the hydrothermal reaction to obtain a solid, grinding and sieving the solid to obtain a porous opal with a particle size of 200-600 mesh, and setting aside; Step 3, dissolving the metal salt of the antibacterial nanomaterial in a methanol solution under light-proof conditions, then adding silica sol and titanium sol thereto, stirring for 2-5 hours, adding porous opal, continuing to stir for 2-6 hours to obtain a mixed solution 2, then adding a sodium borohydride aqueous solution to the mixed solution 2, stirring at high speed for 2-4 hours, centrifuging and separating the solid, washing the solid, and vacuum drying to obtain a silicon-titanium self-cleaning agent; The silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, aminopropyl trimethoxysilane, aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane; The titanium source is one or more of tetraethyl titanate, tetrabutyl titanate, and tetraisopropyl titanate; The metal salt of the antibacterial nano material is silver nitrate.

2. The formaldehyde-free powder coating for MDF according to claim 1, characterized in that: The epoxy resin is one or more of E-06, E-12, and E-20 epoxy resins; and the acid value of the polyester resin is 30-60 mgKOH / g.

3. The formaldehyde-free powder coating for MDF according to claim 1, characterized in that: The polyester resin is specifically selected from one or more of DSM Uralac P3050, Excalibur SJ6711, and Excalibur SJ6722.

4. The formaldehyde-free powder coating for MDF according to claim 1, characterized in that: The mass ratio of the epoxy resin to the polyester resin is 0.7:1-1:0.

7.

5. The formaldehyde-free powder coating for MDF according to claim 1, characterized in that: The mass percentage of the silicon source and the titanium source in the silica sol and the titanium sol is 1-6%; the mass ratio of the silica sol to the titanium sol is 0.5:1-1:

1.

6. The formaldehyde-free powder coating for MDF according to claim 1, characterized in that: The curing accelerator includes one or more of 2-methylimidazole, 2-phenylimidazole, and 2-ethyl-4-methylimidazole.

7. The method for preparing the formaldehyde-free powder coating for MDF according to any one of claims 1 to 6, characterized in that: The steps include: Step S1: weighing various raw material components of the powder coating according to the preparation formula, adding them into a mixer, and mixing them evenly to obtain a mixture; Step S2: adding the mixed material into a twin-screw extruder for extrusion at a temperature of 80-110° C.; Step S3: tabletting, cooling, crushing and screening the extruded material, and selecting powder with a D50 particle size of 30-50 μm to obtain a finished powder coating product.

8. The use of the formaldehyde-free powder coating for MDF according to any one of claims 1 to 6, characterized in that: Used for coating of medium density fiberboard.